Sincretismo e circolarità in Bobby McFerrin. Tra vocalità, gioco e improvvisazione (De Musica, 2022)
In this article, I will discuss the synthesis of seemingly incompatible elements which forms Bobby McFerrin’s aesthetics and ethics. I suggest that such synthesis represents his personal interpretation of a “circular” vision of existence. To support this idea, I will introduce the three fils rouges that cross his work, and I will analyse their crucial importance for such “syncretic circularity”. First, the vocality, at the crossroads of different musical traditions, e.g., the African, the Afro-American and the European. Second, the playful approach to music, and to the audience that is conceived of as an integral part of the performances. Third, the improvisational practice that links all the musical traditions he goes through. Finally, I will discuss McFerrin’s work in terms of the Pareysonian aesthetics, thanks to which improvisation can become paradigm of the artistic doing, and within a perspective that sees improvisation as paradigm of the human action tout court.